Relationship of neck circumference and difficult endotracheal intubation in obese patients - Karna, Amit Kumar; Bashir, Khalid (Janaki Medical College Journal of Medical Science, 2017)
Background and Objectives: Patient identification with difficult intubation is important in planning anesthetic management and one major factor for difficult intubation in t he obese patients is large neck circumference. The need for prediction of a potentially difficult airway received great importance as it plays a significant role in reducing morbidity and mortality. Therefore, this study was done to glimpse the effect of neck circumference on endotracheal intubation and to determine the frequency of difficult intubation. Material and Methods: The study was cross sectional descriptive study and convenient sampling technique was used. Seventy patients of age between 19-50 years of both sexes were enrolled. Neck circumference was measured at the level of cricoid cartilage along with other airway assessments. Direct laryngoscopy was done and checked whether it is difficult one or easy using Intubation difficulty scale. Data were entered and analyzed by using statistical software SPSS version 15.0. Results: Mean BMI was noted as 33.02±2.30 kg/m2 and the mean neck circumference was 43.64±2.30 cm. Difficult intubation was observed in 23 (32.86%) patients with mean neck circumference of 45.44±1.88 cm and normal intubation observed in 47(67.14%) patients with mean neck circumference of 42.77±1.98 cm. Linear correlation was found between the neck circumference and Intubation Difficulty Scale score with value of Pearson correlation=0.617 . Conclusion: Neck circumference of patient was found to have significant effects on difficult intubation. Frequency of difficult intubation was found in almost one third of obese patients with increasing neck circumference. Janaki Medical College Journal of Medical Sciences (2016) Vol. 4 (2): 3-9